2016
DOI: 10.4317/medoral.21233
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between -889 C/T polymorphism in interleukin-1A gene and risk of chronic periodontitis: Evidence from a meta-analysis with new published findings

Abstract: BackgroundPeriodontitis results from an inflammatory response caused by accumulative microorganisms in periodontal sites. Several factors are involved in pathogenesis of periodontitis, for example the -889 C/T polymorphism in interleukin-1A gene. This study aimed to evaluate the relationship between this polymorphism and risk of development of chronic periodontitis by a meta-analysis based in new published findings.Material and MethodsThereunto a review in literature was performed in the electronic biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
2
16
1
Order By: Relevance
“…7,8 On the other hand, many studies have suggested that genetic polymorphisms including single nucleotide polymorphisms (SNPs) in IL-1 and TNF-α genes are associated with susceptibility to periodontitis or severity of periodontal disease. [9][10][11][12][13][14] Among the SNPs known to be associated with periodontitis, IL-1α + 4845, IL-1β + 3954, and TNF-α −863 have been extensively investigated, 11,[15][16][17][18] and several comprehensive meta-analyses reported that risk of periodontitis is significantly associated with SNPs of IL-1 (IL-1α + 4845 and IL-1β + 3954) 9,[19][20][21][22][23][24] or TNF-α −863 polymorphism. 10 However, the previous studies were examined mainly in Caucasians and several Asian populations including Chinese, Japanese, and Indians.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 On the other hand, many studies have suggested that genetic polymorphisms including single nucleotide polymorphisms (SNPs) in IL-1 and TNF-α genes are associated with susceptibility to periodontitis or severity of periodontal disease. [9][10][11][12][13][14] Among the SNPs known to be associated with periodontitis, IL-1α + 4845, IL-1β + 3954, and TNF-α −863 have been extensively investigated, 11,[15][16][17][18] and several comprehensive meta-analyses reported that risk of periodontitis is significantly associated with SNPs of IL-1 (IL-1α + 4845 and IL-1β + 3954) 9,[19][20][21][22][23][24] or TNF-α −863 polymorphism. 10 However, the previous studies were examined mainly in Caucasians and several Asian populations including Chinese, Japanese, and Indians.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of oral diseases, there is the periodontitis, characterized as an immune-inflammatory disease as response to the presence of microorganisms in periodontal sites [14]. The pathogenesis of periodontitis receives influence of several factors including the colonization of periodontal sites by gram-positive and gram-negative bacteria species oral hygiene and genetic variations [15][16][17][18][19]. Both periodontitis and H. pylori infection had considerable worldwide prevalence and are associated with systemic conditions [8,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Gene-related studies have confirmed that chronic periodontitis and aggressive periodontitis may be two different diseases [12], and interleukin (IL) gene polymorphisms possibly play a pivotal role in the occurrence and progression of chronic periodontitis [13][14][15]. The genes in IL-1 family have allele polymorphisms which may be related to the susceptibility of chronic periodontitis, in which single nucleotide polymorphism (SNP) -889C/T (rs1800587) in IL-1A gene is researched extensively [16][17][18][19]. IL-1A (-889C/T) is an SNP located at the position -889 upstream of translation start, and its polymorphism has a potential functional importance through the regulation on the IL-1 protein production [20].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a lot of studies have investigated the association between IL-1A (-889C/T) polymorphism and chronic periodontitis, but the results are inconsistent [16-18, 21, 22]. A previous meta-analysis reported that IL-1A (-889C/T) polymorphism was related to the susceptibility of chronic periodontitis, but the included studies were miscellaneous and Hardy-Weinberg equilibrium (HWE) test was not carried out [19]. Herein, an updated meta-analysis was conducted based on the currently available evidence, with the purpose of further clarifying the association between IL-1A (-889C/T) polymorphism and chronic periodontitis.…”
Section: Introductionmentioning
confidence: 99%